(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Ways perfections o f skills of stylyzatsyy o f forms of drawing from nature in decorative in the process of implementation by the students of the KHGF creative tasks in the techniques of decorative tekstylya. The problem of transformation of model forms in decorative at implementation of creative tasks by the students KHGF is examined in the article.